Buckling optimization of elastic IPE and circular sections columns considering boundry condition effects - M. Mirtaheri; H. Asadi; M. Nazeryan; M. Mirjalaly (Numerical Methods in Civil Engineering)
Abstract: The theory of optimization has improved remarkably during the last four decades. The main part of optimizing investigations has been focused on enhancing buckling resistance which does not violate the economic feasibility of final design. The finite element analysis which is called ESO (Evolutionary Structural Optimization) is presented for optimum (or most ideal) design of columns to increase the buckling resistance of structures. To attain the significant design variables, this method can be employed to choose an appropriate, affective and economical way. During an iterative process, the above approach ensures the attainment of global maximum critical load under the imposed equality volume constraint, type of boundary conditions and type of cross sections. Precise results and numerical examples have been shown and useful diagrams have been developed for the cases of simple, clamped and clamped free supported by different types of cross-sectional areas. The model has succeeded in arriving at the global optimal column designs possessing the absolute maximum buckling load without violating the economic feasibility requirement. As a matter of fact, the cross sectional area of column changes whereas, the total volume of column remains constant. As a result, the buckling forces increase. According to this study critical buckling load of columns decreases by changing the boundary condition from clamped to clamped free and then simply supported.